Cooperative Games and Access to Information from the University Extension - Calvo Sánchez, Loirette (2017)
From the project of academical extension “Knowledge, Peace and Social Management” during the month of November of 2016 a workshop in the community of Guararía in Heredia, Costa Rica titled in Spanish as “Cada Pollo Con Su Rollo” was developed. In which twelve women in between the ages of 12 and 18 and six boys in between the ages 10 and 17 participated. Using simple language, the cooperative game was used as a participative methodology, with the purpose of accessing information and informal alphabetization processes in the subject of human rights. As a result, the participants identified the existence of a grouping of rights captured in the Universal Declaration of Human Rights, that empowers them to live and actively participate in their communities no matter what their economic, social and cultural condition might be.